Bone marrow stroma cells promote a S100A8/A9high subset of chemoresistant AML blasts with distinct metabolic features in a Jak/STAT-dependent manner - Böttcher, Martin; Panagiotidis, Konstantinos; Mentz, K.; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Bone marrow stroma cells promote induction of a chemoresistant and prognostic unfavorable S100A8/A9high AML cell subset. - Böttcher, Martin; Panagiotidis, Konstantinos; Bruns, Heiko; Stumpf, Martina; Völkl, Simon; Geyh, Stefanie; Dietel, Barbara; Schroeder, Thomas; Mackensen, Andreas; Mougiakakos, Dimitrios (Blood Advances, 2022)
The bone marrow (BM) stroma represents a protective niche for acute myeloid leukemia (AML) cells. However, the complex underlying mechanisms remain to be fully elucidated. We found 2 small, intracellular, calcium-sensing molecules, S100A8 and S100A9, among the top genes being upregulated in primary AML blasts upon stromal contact. As members of the S100 protein family, they can modulate such cellular processes as proliferation, migration, and differentiation. Dysregulation of S100 proteins is described as a predictor of poor survival in different human cancers, including increased S100A8 expression in de novo AML. Thus, we wanted to decipher the underlying pathways of stroma-mediated S100A8/A9 induction, as well as its functional consequences. Upregulation of S100A8/A9 after stromal cross talk was validated in AML cell lines, was contact independent and reversible and resulted in accumulation of S100A8/A9high cells. Accordingly, frequency of S100A8/A9high AML blasts was higher in the patients' BM than in peripheral blood. The S100A8/A9high AML cell population displayed enhanced utilization of free fatty acids, features of a more mature myeloid phenotype, and increased resilience toward chemotherapeutics and BCL2 inhibition. We identified stromal cell-derived interleukin-6 (IL-6) as the trigger for a Jak/STAT3 signaling-mediated S100A8/A9 induction. Interfering with fatty acid uptake and the IL-6-Jak/STAT3 pathway antagonized formation of S100A8/A9high cells and therapeutic resistance, which could have therapeutic implications as a strategy to interfere with the AML-niche dynamics.
EVALuna2:503901

Microenvironmental Triggers Induce a Chemoresistant, Differentiated Subset of S100A8/A9(high) AML Cells Via the Jak/STAT3 Signaling Axis - Böttcher, Martin; Panagiotidis, Konstantinos; Mentz, Kristin; Völkl, Simon; Bruns, Heiko; Slany, Robert; Mackensen, Andreas; Mougiakakos, Dimitrios (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

Palmitoylated Proteins on AML-Derived Extracellular Vesicles Promote Myeloid-Derived Suppressor Cell Differentiation via TLR2/Akt/mTOR Signaling - Tohumeken, Sehmus; Böttcher, Martin; Stoll, Andrej; Loschinski, Romy; Panagiotidis, Konstantinos; Braun, Martina; Saul, Domenica; Baur, Andreas; Bruns, Heiko; Mackensen, Andreas; Jitschin, Regina; Mougiakakos, Dimitrios; et al. (Cancer Research, 2020)
Acute myeloid leukemia (AML) represents the most common acute leukemia among adults. Despite recent progress in diagnosis and treatment, long-term outcome remains unsatisfactory. The success of allogeneic stem cell transplantation underscores the immunoresponsive nature of AML, creating the basis for further exploiting immunotherapies. However, emerging evidence suggests that AML, similar to other malignant entities, employs a variety of mechanisms to evade immunosurveillance. In light of this, T-cell inhibitory myeloid-derived suppressor cells (MDSC) are gaining interest as key facilitators of immunoescape. Accumulation of CD14(+) HLA-DRlow monocyticMDSCs has been described in newly diagnosed AML patients, and deciphering the underlying mechanisms could help to improve anti-AML immunity. Here, we report that conventional monocytes readily takeup AML-derived extracellular vesicles (EV) and subsequently undergo MDSC differentiation. They acquired an CD14(+)HLA-DRlow phenotype, expressed the immunomodulatory indoleamine-2,3-dioxygenase, and upregulated expression of genes characteristic for MDSCs, such as S100A8/9 and cEBP beta. The Akt/mTOR pathway played a critical role in the AML-EV-induced phenotypical and functional transition of monocytes. Generated MDSCs displayed a glycolytic switch, which rendered them more susceptible toward glycolytic inhibitors. Furthermore, palmitoylated proteins on the AML-EV surface activated Toll-like receptor 2 as the initiating event of Akt/mTOR-dependent induction of MDSC. Therefore, targeting protein palmitoylation in AML blasts could block MDSC accumulation to improve immune responses.
CRIS-Team WoS Importer:2020-09-25

Stroma Cells Promote a S100A8/A9(high)-Subset of AML Blasts with Distinct Metabolic Features in a Jak/STAT3-Dependent Manner - Böttcher, Martin; Panagiotidis, Konstantinos; Mackensen, Andreas; Mougiakakos, Dimitrios (BLOOD, 2018)
CRIS-Team WoS Importer:2019-02-27

Stroma cells promote a S100A8/A9(high) subset of chemoresistant AML blasts with distinct metabolic features in a Jak/STAT-dependent manner - Böttcher, Martin; Panagiotidis, Konstantinos; Mentz, K.; Popp, Sebastian; Geyh, S.; Jaeger, P.; Schroeder, T.; Bruns, Heiko; Mackensen, Andreas; Mougiakakos, Dimitrios; Völkl, Simon (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23